Stone/tissue differentiation during intracorporeal lithotripsy using diffuse white light reflectance spectroscopy: In vitro and clinical measurements. Issue 8 (18th August 2014) - Lange, Birgit; Jocham, Dieter; Brinkmann, Ralf; Cordes, Jens
<x xml:space="preserve">Abstract</x> Background and Objective Holmium laser lithotripsy is the 'gold standard' for intracorporeal fragmentation of stones. However, there is a risk of damaging and perforating the ureter wall when the laser is accidentally fired while the fiber is in contact with tissue. The aim of this study was to evaluate if white illumination light, diffusely reflected back into the treatment fiber and spectrally analyzed, can be used for differentiating between stone and tissue. Study Design/Materials and Methods Firstly, in vitro reflectance spectra (Xenon light source, wavelength range λ = 350–850 nm) of 38 human kidney stones, porcine renal calix and ureter tissue were collected. Secondly, in an in vivo study with 8 patients, 72 ureter and 49 stone reflectance signals were recorded during endourological interventions. The spectra were analyzed to discriminate between stone and tissue by the absence or presence of minima due to hemoglobin absorption at λ1 = 542nm and λ3 = 576nm. Results In vitro, all stone and tissue signals could correctly be identified by calculating the ratio R = I (λ1 = 542 nm)/I (λ2 = 475 nm): Because of the hemoglobin absorption at λ1, R is smaller for tissue than for calculi. In vivo, only 75% tissue spots could correctly be identified utilizing this method. Using the more sophisticated evaluation of looking for minima in the diffuse reflectance spectra at λ1 = 542 nm and λ3 = 576 nm, 62 out of 64 tissue spots were correctly identified (sensitivity 96.9%). This was also the case for 39 out of 43 stone spots. Taking into account the number of measured spectra, a tissue detection probability of 91% and a stone detection probability of 77% was achieved (significance level 5%). Conclusion White light diffusely reflected off the treatment zone into the fiber can be used to strongly improve the safety of Holmium laser lithotripsy by implementing an automatic feedback control algorithm that averts mispositioning the fiber. Lasers Surg. Med. 46:614–619, 2014. © 2014 Wiley Periodicals, Inc.